MANAGEMENT OF PROXIMAL HUMERUS FRACTURES IN ADULTS - Ferdiansyah, Ricky; Pratama, Alvin; Yulanda Putra, Yosie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Proximal humerus fractures, more common in women and increasingly prevalent with age due to falls, pose a challenge in orthopaedic care, often leading to persistent pain and reduced shoulder function. This systematic review aims to evaluate diverse management strategies for these fractures in adults, analysing their effectiveness, complications, and patient-reported outcomes to guide treatment decisions. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result Our search produced 13 results. After looking at the titles and summaries, we found several papers that fit our criteria. At first, we excluded few articles because they were written in review and case report style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included prospective, retrospective studies, and prospective randomized control trial study. Conclusion: This comprehensive study compared ORIF, HA, and RSA in PHF patients, revealing that ORIF was preferred in younger patients with simpler fractures, while RSA was favoured in older patients with complex fractures. ORIF demonstrated better motion than HA, but higher reoperation rates were noted for ORIF and HA compared to RSA, essential information for patient discussions. Postoperative fractures were prevalent, highlighting a need for counselling to prevent future falls and fractures post-PHF treatment. Despite prior inconclusive studies, the need to reduce unnecessary surgeries, especially in the elderly, remains crucial to minimize complications and healthcare costs amidst the shifting treatment landscape.